Analytical Optimization for the Warehouse Sizing Problem Under Class-Based Storage Policy (2016)
The aim of this paper study the impact of class-based storage policy based on the optimal configuration of U-flow single command warehouses using a on an ABC product classification. For that purpose, the authors propose a non linear optimization model to minimize the expected travel distance of the warehouse and use analytical methods to solve it. The most important contribution is to provide a mathematical proof that regardless of the storage policy (It does not matter the specifics of the turnover pattern of the products), the optimal warehouse has a width that is the double of its length, and the pick and deposit point should be located in the middle of the width of the warehouse. In addition, authors perform a sensitivity analysis that indicates that the optimal solution is robust, meaning that a certain deviation from the optimum layout does not impose a significant penalty on the expected travel distance of the warehouse.